2016
DOI: 10.1111/ppa.12596
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring infection of tomato fruit by Tomato yellow leaf curl virus

Abstract: Fruit constitutes a strong sink organ and thus accumulates infecting viruses, but there is limited information about the infection process of viruses in fruit. Tomato yellow leaf curl virus (TYLCV, genus Begomovirus, family Geminiviridae) is one of the most important viruses affecting the production of tomato fruit. Using real-time quantitative PCR, TYLCV was shown to accumulate with increasing titres in early developing tomato fruit tissues from anthesis until 21 days post-anthesis. In situ hybridization demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The same is true for virus-localization studies in seeds and embryos, often considered the proof for seed transmissibility. Indeed, TYLCV DNA has been detected in the embryos of infected tomato seeds using in situ hybridization [ 35 ], a technique that cannot selectively discriminate if whole molecules are present in the observed tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The same is true for virus-localization studies in seeds and embryos, often considered the proof for seed transmissibility. Indeed, TYLCV DNA has been detected in the embryos of infected tomato seeds using in situ hybridization [ 35 ], a technique that cannot selectively discriminate if whole molecules are present in the observed tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Whitefly transmission of TYLCV was also observed from symptomatic and asymptomatic seedlings raised from infected seeds to healthy tomato plants, which strengthen the concept that offsprings from infected tomato plant can act as a source of inoculum for B. tabaci-mediated transmission. Just et al (2017) demonstrated the localization of TYLCV DNA and transcripts of the CP gene specifically to the phloem tissue of young fruit, sepals, petals, and embryo of developing tomato seed through in situ hybridization experiments. The accumulation of TYLCV with increasing titers was observed in early developing tomato fruit tissues from anthesis until 21 days post-anthesis through qPCR (Kil et al, 2017(Kil et al, , 2018.…”
Section: Past Knowledge Of Begomovirus Seed Transmissionmentioning
confidence: 98%